Analysis of Teachers' Difficulties in Implementing P5 Lessons to Elementary School Students - Fauziah, Weniar; Ramadan, Zaka Hadikusuma (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
The Pancasila Student Profile Strengthening Project (P5) is an important program in the Independent Curriculum that requires teachers to actively participate in the planning, implementation, and evaluation of project-based learning. However, the implementation of this program in elementary schools still faces various obstacles. This study aims to analyze teachers' difficulties in implementing P5 for fifth-grade students at Air Putih 008 Public Elementary School, Indragiri Hulu Regency. The study used a qualitative approach with data collection techniques through observation, structured interviews, and documentation. Data validation was carried out using triangulation of sources, time, and techniques. The research subjects were fifth-grade teachers directly involved in the implementation of P5. Data analysis used the Miles and Huberman interactive model, which includes data collection, reduction, presentation, and drawing conclusions. The results showed that teacher difficulties occurred at three main stages. At the planning stage, teachers did not fully understand the concept of P5, so the objectives and flow of activities were still general and lacked detail, compounded by minimal technical training. At the implementation stage, obstacles arose due to limited time, facilities, and uneven student participation in group work. During the evaluation phase, assessments tend to focus on the final project results without optimizing the assessment of the process, character indicators, and portfolios. The main factors influencing these constraints include limited training, minimal supporting facilities, and the lack of comprehensive character assessment instruments. The conclusion of this study emphasizes the need for ongoing training for teachers, the provision of adequate facilities, and the development of a structured evaluation system to ensure more effective implementation of P5 in elementary schools.